The sedimentology of debris within basal ice, the source of material for the formation of lodgement till: an example from the Russell Glacier, West Greenland - Baltrūnas, Valentinas; Šinkūnas, Petras; Karmaza, Bronislavas; Česnulevičius, Algimantas; Šinkūnė, Eglė (Geologija, 2009)
The grain-size distribution of material within the basal ice reflects a combination of the petrology of the eroded glacier bed and by debris comminution and mixing associated with ice deformation. During glacier movement, debris material is mechanically milled to a silt fraction. Clay particles appear only when a glacier flows across clayrich subglacial beds. The increase of the value of relative entropy (index of mixing) of grain-size distribution of eroded material is associated with equalization of the content of debris of different fractions in the mixing process (if the content of all fractions would be equal, the value of relative entropy would be one). The basal ice of glaciers can be viewed as the initial stage of lodgement till formation occurring during plastic flow of glacier which in turn strongly influences the grain-size structure of lodgement till.